Experimental Test Procedure of the Spatial Distribution of Environmental Parameters and Products of Combustion in a Residential Area and Adjacent Spaces - A. A. Antoshyn; S. A. Volkau (Приборы и методы измерений)
This article is dedicated to the issue of efficiency increase of fire detection equipment in living accommodation and adjacent spaces. This research is intended to develop the testing methodology for spatial pattern of combustion products, including toxic gases with asphyxiant and irritant effects, in both height and area of rooms in a standard apartment building, as well as correlation identification between controlled by fire alarm parameters of environment in living rooms and dangerous fire factors.Proposed methodology includes the concentration measurement of the basic gaseous combustion products (asphyxiant and irritant), generated in the process of materials burning in living accommodation. Justification of measurement facilities location in the fire scene and adjacent spaces is provided, considering the most likely position of a person during the evacuation and leisure time. The impact of fire stage on the flow rate of optical radiation diffused by smoke is shown.The findings will enable to develop the testing methodology for fire detectors designed to protect living accommodations and people located in them, formulate the functioning effectiveness criteria (operation algorithms) for detectors, used in living accommodations.